The importance of understanding web frameworks for statisticians - Hakim, R B Fajriya; Sugiyarto, Sugiyarto (Bulletin of Applied Mathematics and Mathematics Education, 2021)
As the web and computational technology carry on growing and huge data are yielded on the web, these technologies are turn into important for a statisticians' work. It is worthy that statistician always gain knowledge of new aspects of computation. A lack of computational reasoning skills gets it hard for statisticians to work in a team. If statistician do not takeÂ up this computations challenge more coherently, statistics will be marginalized and take away related at a time when its data science reputation grow up significantly. In addition, people rely on the information on web, for whatever their reason.Since web growth, several major transforms have evolved, from the most rudimentary concept until a new model of interaction between humans and machines. Simple interactivity denotes that users can enter data to the application on a web page, then click on button, and then appears a new web page with the results of the computations. This application has been known as web application with most are built with the utility of web frameworks which is a package of programming tasks that offering services through the Internet. Therefore, this paper gives short overview the importance of Flask web frameworks to assist the lack of computational skill of statistician over web application in the simplest possible way and how web framework is used to create a web page with application form, run the application to compute statistical calculation which has been deployed in local server, and produce a web page with the solutions